Strategic masculinities: Vulnerabilities, risk and the production of prison masculinities. (November 2015) - Ricciardelli, Rosemary; Maier, Katharina; Hannah-Moffat, Kelly
Expressions of masculinity in prison are most often characterized as being structured in response to an environment that encourages displays of stoicism, bravery, physical prowess and violence/aggression. However, we found that the antagonistic, precarious and risk-prone environment of the prison shapes prisoners' behaviours and the constitution of 'normative' and hegemonic masculinities in more nuanced ways than prior research suggests. Drawing on in-depth interviews with 56 male parolees, we explored how these men perceived and responded to risk while incarcerated, as well as how prison masculinities are linked with experiences and management of risk to their personal (legal, physical and emotional) safety. In this article, we focus on how prisoners mobilized and negotiated their masculine subjectivities to handle the uncertainty of imprisonment and the various risks they encountered in prison. We argue that penal risks and prison masculinities are mutually constitutive; risk is linked to perceptions of physical and emotional vulnerability, which shape prisoners' masculine embodiment. Simultaneously, prisoners try to respond to uncertainty and perceived risk in ways that present their masculinity as empowered rather than submissive. Our findings advance the conceptualization of prison and hegemonic masculinities, penal environments and risk/uncertainty.